KONTRIBUSI USAHA JAJANAN KUE TERHADAP PENDAPATAN RUMAH TANGGA DI DESA NAIN KECAMATAN WORI KABUPATEN MINAHASA UTARA - Daniel ., Koibur; Gene H. M. Kapantow; Leonardus R. Rengkung (AGRI-SOSIOEKONOMI, 2017)
This study aims to see how big the level of business benefits of snack cake and its contribution to household income. This research was conducted in October until December 2016. The data used are primary data and secondary data. This research was conducted by direct interview technique with 15 (fifteen) respondents in this case cake snack businessman and also using written data in document form obtained from village head. The data obtained will be analyzed using descriptive analysis and will be presented in tabular form. The results of this study indicate that the average cake snack profit is Rp.4.503.835 in 1 (one) month, while the contribution of cake snack business to household income has a percentage of 83.65% in 1 (one) month.